Demand-side mobile money drivers of financial inclusion: Minimum economic growth thresholds for mobile money innovations - Simplice Asongu; Raufhon Salahodjaev (African Governance and Development Institute (AGDI), 2022)
This study provides minimum economic growth (or GDP growth) critical masses or thresholds that should be exceeded in order for demand-side mobile money factors to favorably drive mobile money innovations for financial inclusion in developing countries. The considered mobile money innovations are: mobile money accounts, the mobile phone used to send money and the mobile phone used to receive money. The empirical evidence is based on Tobit regressions. For positive net relationships that are established, an extended analysis is engaged to provide minimum GDP growth levels required to sustain the positive net nexuses. From this extended analysis, in order for economic growth to modulate demandside mobile money drivers to favorably influence mobile money innovations, minimum GDP growth rates are: (i) 3.875% for the nexus between bank accounts and the mobile phone used to send money; (ii) 3.769 % for the relationship between automated teller machine (ATM) penetration and the mobile used to send money and (iii) 3.666% for the nexus between ATM penetration and the mobile phone used to receive money.
Keywords: D10; D14; D31; D60; O30; 330; Mobile money; technology diffusion; financial inclusion; inclusive innovation